Perception v. actual intakes of junk food and sugar-sweetened beverages in Australian young adults: assessed using the mobile food record. Issue 13 (5th June 2017) - Harray, Amelia J; Boushey, Carol J; Pollard, Christina M; Panizza, Chloe E; Delp, Edward J; Dhaliwal, Satvinder S; Kerr, Deborah A
Abstract: Objective: To determine perception v . actual intakes of energy-dense nutrient-poor 'junk food' (JF) and sugar-sweetened beverages (SSB) in young adults, using the mobile food record (mFR). Design: Before-and-after eating images using a 4 d mFR were assessed for standardised 600 kJ (143 kcal) servings of JF and SSB (excluding diet drinks). Participants reported their concern about the health aspects of their diet, perceptions and intentions regarding JF and SSB. Setting: Perth, Western Australia. Subjects: Adults ( n 246) aged 18–30 years. Results: The mean (sd ) intake of JF+SSB was 3·7 (2·0) servings/d. Women thinking about drinking less SSB consumed more SSB servings/d (1·5 (1·2)) than men (0·7 (0·5); P <0·05) who were thinking about drinking less. Men not thinking about cutting down JF consumed more servings/d (4·6 (2·4)) than women (2·5 (0·7); P <0·01) who were not thinking about cutting down. Those who paid a lot of attention to the health aspects of their diet consumed less JF+SSB than those who took only a bit of notice ( P <0·001), were not really thinking much about it ( P <0·001) or who didn't think at all about the health aspects of food ( P <0·01). Conclusions: Perceptions and attitudes regarding JF and SSB were associated with level of consumption. Those not thinking about cutting down their intake of these foods represent an important target group as they consume more than their peers. Further research is needed to identify how amenable young adults are to changing their intake, particularly given the lack of attention paid to the health aspects of their diet.